MANAJEMEN WAKTU MENJADI KUNCI NILAI UNGGUL: INOVASI EDUKASI UNTUK MAHASISWA AKUNTANSI BERPRESTASI - Aryani, R. Ayu Ida; Muliani, Muliani; Nukman, Nukman (STIE Pelita Nusantara, 2025)
Time management is an important skill that affects students' academic success. This community service program aims to provide education about the importance of time management to students of the Bumigora University Accounting Study Program. This activity aims to overcome common problems among students, namely difficulties in managing time effectively for lecture activities, assignments, organizations, and personal lives. The approach used includes socialization, interactive discussions, and training on the use of tools such as to-do lists, priority matrices, and digital time management applications. This training has succeeded in increasing students' understanding of the importance of time management and their ability to manage study schedules and other activities. Evaluation through questionnaires and participant reflections showed that most participants felt more directed, disciplined, and able to complete tasks on time after participating in the training. In addition to academic impact, the program also contributes to the formation of positive character, such as responsibility and independence. Time management education can be an effective innovation in supporting students to achieve superior achievements. This activity is expected to be a model of continuous education that can be applied in various other study programs to form a generation of students who are skilled, independent, and highly competitive.Keywords: time management, academic achievement, students, accounting, community service